Mentoring students engaging in scholarly projects and dissertations in doctoral nursing programs - Anderson, Kelley M.; McLaughlin, Maureen Kirkpatrick; Crowell, Nancy A.; Fall-Dickson, Jane M.; White, Krista A.; Heitzler, Ella T.; Kesten, Karen S.; Yearwood, Edilma L. (Nursing outlook, 2019)
•Faculty provided a mean of 516 and 180 total hours mentoring each PhD and DNP student on their scholarly work, respectively.•Forty percent of faculty received no workload credit for chairing student doctoral committees.•Only 20-25% of faculty reported receiving formal training for the mentoring role.•Faculty retirement trends, increasing number of doctoral nursing students, and the duration of the BSN-DNP program are projected to increase mentoring demands.•Guidelines for the quality of DNP projects and the quantity of students mentored by individual faculty should be established. Doctor of Nursing Practice (DNP) programs in the US have grown exponentially, outnumbering Doctor of Philosophy (PhD) in Nursing programs. Faculty are mentoring increasing numbers of students on DNP projects or PhD dissertations. This descriptive study explored faculty characteristics and examined support, engagement, and outcomes of American Association of Colleges of Nursing member nursing faculty mentoring student DNP projects or PhD dissertations. A researcher-developed survey tool was emailed to 550 Deans and Program Directors of AACN doctoral programs for distribution to their doctoral faculty. Survey data were analyzed using descriptive statistics. 177 DNP and 53 PhD (N=230) program surveys were completed. Faculty described challenges in the mentoring role including: time constraints, workload allocation, resources, faculty role preparation, student readiness, and variability in student outcomes. Additional dialogue and consensus is required to promote mentoring of students in nursing doctoral programs to ensure rigor of scholarly outcomes.